Advancing Public Interests Priorities Within Investee Companies Through Institutional Shareholder Engagement - Angelia, Alissa (Business and Human Rights Law & Policy, 2026)
Shareholders, as providers of risk capital, are entitled to participate in corporate decision-making. However, the existence of the investment chain often limits the influence of individual investors. In contrast, institutional investors, acting as fiduciaries and long-term market participants, are uniquely positioned to shape managerial behaviour, counterbalance executive power, and promote sustainable, stakeholder-oriented corporate practices. Owing to these capacities, institutional shareholders play a significant role in advancing public interest priorities through their investment activities. This article examines how institutional shareholders can engage effectively with investee companies to promote public interests, employing a doctrinal research methodology. It finds that institutional shareholder engagement enhances companies’ financial and non-financial performance, ultimately generating positive public interest outcomes. Engagement may occur through soft forms of interaction or more formal mechanisms, each enabling meaningful stewardship. Consequently, institutional shareholders possess both the capacity and the opportunity to influence corporate conduct and advance public interest priorities through active and responsible engagement